THE EFFECT OF FEVER ON ACETYLATION RATIO AND SULFADIAZINE ELEMINATION KINETICS OF LOCAL SHEEP (Ovis aries) - Ida Tjahajati; Subronto Prodjoharjono; Budiono Santoso (Jurnal Sain Veteriner, 1998)
A Study has been conducted to identify effect of fever towards acetylafion ratio and eleminatkm kinetics of sulfadiazine in sheep. The siudy consist 10 healthy sheep using crossover design. Each animal was treated twice with 40 days interval. In the first treatment the sheep were given 2 gram of sulfadiazine and 0.4 gram pyrimethamine. In the second treatment the animals were treated fever induction prior to treatment using 2 gram of sulfadiazin and 0.4 gram pyrimethamine. Blood samples were taken From jugular vein in hour of 0, 0.08.0.25, 0.5, 1,2,4,6,9.12, 18, and 24. Plasma sulfadiazine levels were analyzed using Bratton-Marshall Methode. Sulfadiazin parameter was calculated using Stripe program. Theresults of the study revealed that fever did not significantly (P>0,05) increased the aceiylation ratio and inhibited elemination of sulfadiazine.